Complementarity of Selective Culture and qPCR for Colistin Resistance Screening in Fresh and Frozen Pig Cecum Samples - Miguela-Villoldo, Pedro; Moreno, Miguel A.; Hernández, Marta; Rodríguez-Lázaro, David; Gallardo, Alejandro; Borge, Carmen; Quesada, Alberto; Domínguez, Lucas; Ugarte-Ruiz, María (Frontiers in Microbiology, 2020)
Retrospective studies involving the screening of frozen stored collections of samples are commonplace when a new threat emerges, but it has been demonstrated that the freeze-thaw process can affect bacterial viability. The study of colistin-resistant bacteria in human and animal samples is an example of this issue. In this study we compared culture-based and PCR-based methods for analysing both relative occurrence and diversity of colistin-resistant bacteria in caecal samples to determine the most appropriate method for frozen samples. Thus, 272 isolates from the caecal contents of healthy pigs were tested before and after a six-month freezing period. A selective medium was used when traditional isolation of colistin-resistant bacteria was tested, while a real-time SYBR Green PCR assay was applied for mcr-1 quantification. The number of samples with colistin-resistant isolates was higher in fresh samples (247/272) than in frozen ones (67/272) and also showed a higher diversity of colistin-resistant genera. PCR identification of mcr colistin resistance genes evidenced that mcr-1 was the most prevalent mcr gene and mcr-2 was detected for the first time in pigs from Spanish animal production. The number of samples with mcr-1-carrying bacteria after a freezing period decreased, while real-time quantitation of the mcr-1 gene showed similar values in frozen and fresh samples. Therefore, when frozen caecal samples need to be analysed, molecular detection of DNA could be the best option to provide a highly representative frame of the initial population present in the sample, and culture-based methods might be a useful complement to study colistin resistance levels.